포트폴리오 평가의 적용이 언어장애 아동의 언어능력 향상에 미치는 효과 - 박선희(Sun-Hee Park) (언어치료연구, 2005)
본 연구는 포트폴리오 평가의 적용이 언어장애아동의 언어능력, 즉 언어이해능력 및 언어표현능력을 향상시키는지를 알아보는데 연구의 목적이 있다. 이를 위하여 언어장애아동 6명을 선정하였고, 이들의 언어능력을 알아보기 위하여 취학 전 아동의 수용 언어 및 표현 언어 발달척도(PRES)를 실시하였다. 사전 사후 실험 설계로 진행하였으며 자료는 사전 사후 t-검정으로 분석하였다. 언어장애 아동에게 포트폴리오 평가를 적용하여 다음과 같은 연구 결과를 얻었다. 첫째, 언어이해 능력에서 대상 아동 모두는 사전 언어이해력 점수에 비하여 사후 점수가 높은 것으로 나타나 언어이해력이 전체적으로 현저한 향상을 보였다. 둘째, 언어표현능력에서 대상 아동 모두는 사전 언어표현력 점수에 비하여 사후 점수가 높은 것으로 나타나 언어표현력이 전체적으로 현저한 향상을 보였다. 이상과 같은 결과를 바탕으로 포트폴리오 평가의 적용이 언어장애 아동의 언어 능력을 향상시키는 알 수 있었다. The purpose of this study was to examine the effects of using portfolios assessment in language comprehension and language expression in children with language impairments. Six 3～5 years old children with the language impairments, participated in the study. None of subjects showed visual, hearing, emotional, and/or behavioral problems besides language impairments. To investigate each subject's language ability, PRES tool was administered. The study used pre and post treatment design and data was collected using anecdotal recording system. To check the effects of the intervention, data was analyzed using t-test. The results showed as follows: First, using the portfolios assessment improved all the subjects' language comprehension ability. Second, using the portfolios assessment improved all the subjects' language expression ability. As described above, using the portfolios assessment improved the language ability for children with language impairments. KCI Citation Count: 3